Adherence to COVID-19 Appropriate Behavior Among Respiratory Therapists: A Cross-Sectional Study in the Kingdom of Saudi Arabia - Noor Al Khathlan; Bijaya Kumar Padhi (Frontiers Media S.A., 2021)
Background: Adherence to novel coronavirus disease 2019 (COVID-19) appropriate behavior plays a crucial element in the management of the infections of COVID-19. Despite the importance of transmission-reducing behaviors among healthcare professionals, there is a lack of literature in this area of research explicitly relating to respiratory therapists (RTs). Therefore, it is essential to assess the adherence level to COVID-19 transmission-reducing behaviors among the RTs in Saudi Arabia.Methods: A web-based online survey was conducted using questions based on the risk assessment guidelines of WHO. A random representative sample of RTs (N = 215) residing in Saudi Arabia was recruited for the study. Descriptive and inferential statistics were computed using STATA software. Logistic regression analysis was used to identify key factors that are associated with adherence to COVID-19 appropriate behavior among the study participants.Results: Of the 215 participants, 59.5% were aged between 26 and 35 years, and 40.9% were women. Most (85.5%) participants had a bachelor's degree while 12.0% had a master's degree. About 56.2% of RTs provided direct care to a confirmed patient of COVID-19 during the study periods. The study showed 80.9% of RTs in Saudi Arabia adhered to personal protective equipment (PPE) at the workplace and 65.0% at home. Moreover, the findings of the study indicated that senior RTs (with >5 years of experience) demonstrated a higher adherence level to the guidelines than RTs with <5 years of experience. High-risk perception [aOR:2.32; 95% CI: 1.09-3.27], and work history of <5 years [aOR:2.00; 95% CI: 1.14-3.15], were found to be the strongest predictors in explaining the adherence to appropriate behavior among the RTs at the workplace. Whereas the high-risk perception [aOR:2.32; 95% CI: 1.09-3.27] and being married [aOR:1.85; 95% CI: 1.08-3.82] were found to be the strongest predictors at home.Conclusion: Adherence ("Always" or "Most times") to COVID-19 appropriate behavior was found to be high at hospital settings among the study participants. However, the same practice was found to be inconsistence in non-healthcare settings among the RTs. Considering the paramount role of COVID-19 appropriate behavior in reducing the transmissions the policy focus, therefore, needs to be on creating a well-spread behavior change communication that is curtailing the adoption of appropriate behavior in the non-healthcare settings.